MODIFIKASI TANAH DAN VARIASI FONDASI BANGUNAN ISTANA MAIMUN, KOTA MEDAN, PROVINSI SUMATERA UTARA - Stanov Purnawibowo; Andri Restiyadi (Berkala Arkeologi Sangkhakala, 2019)
Maimun Palace is one of the iconic cultural heritage buildings in Medan City, North Sumatra Province. It has a unique blend of Malay and colonial styles. The subject in this article deals with the building foundations of the Maimun Palace. The foundation part has a crucial role in a building, but it is rarely used as a research topic. The issues raised in this paper relate to the structure, composition, and function of the foundation. The purpose of writing this article besides answering the problem is also expected to be able to increase architectural treasury, especially regarding the style of building foundations that have a blend of traditional Malay and Colonial styles. Through descriptive-analytical research, the conclusion obtained from this study is that there are three kinds of building foundations that adjust to the function of supporting the buildings above which consist of one, two and three levels of the building.